CHEMICAL KNOWLEDGE IN CLINICAL MEDICAL SPECIALTIES - V. Hadzhiiliev; L. Hadzhiilieva (Science & Research)

(untitled)
In a number of publications, a team of lecturers from the Faculty of Medicine of Trakia University – Stara Zagora studies how the basic knowledge of chemistry, gained in the course in "Medical Chemistry", is used in other medical disciplines, both preclinical and clinical. The process is bidirectional because students receive new knowledge in chemistry. To establish these interactions, explored and compared is the curricula, lecture courses, practical hours and basic teaching aids in "Medical chemistry" and the other disciplines of the FM curriculum. This article discusses the importance and application of chemical knowledge in internal diseases and in clinical medical specialties.